2012
DOI: 10.1027/1016-9040/a000113
|View full text |Cite
|
Sign up to set email alerts
|

Young Diaspora Immigrants’ Attitude and Behavior Toward the Host Culture

Abstract: Positive attitudes toward contact with members of the host culture, host-culture language usage, and social relations with natives are frequently used criteria for assessing immigrants’ host-culture participation. Precursors of these criteria are, however, rarely studied, especially from a longitudinal perspective. We expected that a strong identification with the host culture or the culture of origin would be associated with higher or lower host-culture participation, respectively, and were able to test these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
(108 reference statements)
1
15
0
Order By: Relevance
“…Again, this may apply even more to ethnic Germans, who share an ethnic foundation with native Germans (Brenick et al 2012, 114). Although ethnic and national identities are negatively related among ethnic Germans as well (Phinney et al 2006;Stoessel, Titzmann, and Silbereisen 2012), ethnic Germans tend to stress the fact that their ethnic heritage is German (Dietz 1999), which should generally favor the adoption of German national identification (Steinbach 2001). Parents of ethnic Germans, as well as the native German population, also support the adoption of ethnic German adolescents into the German society (Titzmann et al 2011).…”
Section: Hypotheses For Main Immigrant Groups In Germanymentioning
confidence: 99%
“…Again, this may apply even more to ethnic Germans, who share an ethnic foundation with native Germans (Brenick et al 2012, 114). Although ethnic and national identities are negatively related among ethnic Germans as well (Phinney et al 2006;Stoessel, Titzmann, and Silbereisen 2012), ethnic Germans tend to stress the fact that their ethnic heritage is German (Dietz 1999), which should generally favor the adoption of German national identification (Steinbach 2001). Parents of ethnic Germans, as well as the native German population, also support the adoption of ethnic German adolescents into the German society (Titzmann et al 2011).…”
Section: Hypotheses For Main Immigrant Groups In Germanymentioning
confidence: 99%
“…Besides focusing on the rarely studied complexities of ethnic and national identification patterns of ethnic migrants (see also Stoessel, Titzmann, & Silbereisen, ), the present study complements previous research by taking into account the role of pre‐migration identities and anticipations for the development of post‐migration identities and outgroup attitudes. Several social psychological studies have shown that the anticipation of the quality of future contact affects the way in which actual contact situations are perceived and intergroup attitudes are formed (e.g.…”
Section: The Effects Of Discrimination On Identities and Attitudesmentioning
confidence: 99%
“…On average, adolescents' identification as 'German' ranged between M = 3.5 and M = 3.6 (SDs = 1.7 to 1.8) and as 'Russian' between M = 3.7 and M = 4.0 (SDs = 1.9 to 2.0), depending on the waves of assessment. Previous empirical analyses verified that cultural identification shows a bidimensional structure among diaspora immigrants from Russia; therefore, identifications with being 'German' and with being 'Russian' can be deemed as independent aspects (Stoessel, Titzmann, & Silbereisen, 2012). Both measures of cultural identification were moderately negatively related (rs ranging between r = -.36 and r = -.49 within the same wave) and showed adequate reliability (test-retest correlations for 'German' ranging between r = .50 and r = .71, and for 'Russian' ranging between r = .51 and r = .65 for subsequent waves).…”
Section: Methodsmentioning
confidence: 99%